(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2025)
This paper delves into the illustrations of Mexican artist Ernesto "El Chango" García Cabral (1890-1968), focusing on depictions of violence in the gender relations. By analyzing his graphics from the 1920s to 1939, the study explores how García Cabral employs the art deco style to portray the "modern girl" of the upper classes. While overlooking the social transformations experienced by women from other social strata, he leverages his high media exposure to diversify the imagery of the period, critiquing the new bourgeoisie and remnants of the Porfiriato regime. Thus, this research sheds light on the non-canonical cultural production of the time and the ideological stances within post-revolutionary Mexico, specifically in relation to gender representations.